A lasting crisis affects R&D decisions of smaller firms: The Greek experience - Ioannis Giotopoulos; Alexander Kritikos; Aggelos Tsakanikas (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
We use the prolonged Greek crisis as a case study to understand how a lasting economic shock affects the innovation strategies of firms in economies with moderate innovation activities. Adopting the 3-stage CDM model, we explore the link between R&D, innovation, and productivity for different size groups of Greek manufacturing firms during the prolonged crisis. At the first stage, we find that the continuation of the crisis is harmful for the R&D engagement of smaller firms while it increased the willingness for R&D activities among the larger ones. At the second stage, among smaller firms the knowledge production remains unaffected by R&D investments, while among larger firms the R&D decision is positively correlated with the probability of producing innovation, albeit the relationship is weakened as the crisis continues. At the third stage, innovation output benefits only larger firms in terms of labor productivity, while the innovation-productivity nexus is insignificant for smaller firms during the lasting crisis.
Keywords: L25; L60; O31; O33; 330; Small firms; Large firms; R&D; Innovation; Productivity; Long-term Crisis